Circadian rhythms of locomotor activity and hippocampal clock genes expression are dampened in vitamin A-deficient rats - Navigatore Fonzo, Lorena Silvina (2014)
The main external time giver is the day-night cycle; however, signals from feeding and the activity/rest cycles can entrain peripheral clocks, such as the hippocampus, in the absence of light. Knowing that vitamin A and its derivatives, the retinoids, may act as regulators of the endogenous clock activity, we hypothesized that the nutritional deficiency of vitamin A may influence the locomotor activity rhythm as well as the endogenous circadian patterns of clock genes in the rat hippocampus. Locomotor activity was recorded during the last week of the treatment period. Circadian rhythms of clock genes expression were analyzed by reverse transcription–polymerase chain reaction in hippocampus samples that were isolated every 4 hours during a 24-hour period. Reduced glutathione (GSH) levels were also determined by a kinetic assay. Regulatory regions of clock PER2, CRY1, and CRY2 genes were scanned for RXRE, RARE, and RORE sites. As expected, the locomotor activity pattern of rats shifted rightward under constant dark conditions. Clock genes expression and GSH levels displayed robust circadian oscillations in the rat hippocampus. We found RXRE and RORE sites on regulatory regions of clock genes. Vitamin A deficiency dampened rhythms of locomotor activity as well as modified endogenous rhythms of clock genes expression and GSH levels. Thus, vitamin A may have a role in endogenous clock functioning and participate in the circadian regulation of the cellular redox state in the hippocampus, a peripheral clock with relevant function in memory and learning.